Unveiling True 3D Nanoscale Microstructural Evolution in Chalcogenide Nanocomposites: A Roadmap for Advanced Infrared Functionality. Issue 9 (24th February 2021) - Kang, Myungkoo; Martin, Isabelle; Sharma, Rashi; Blanco, Cesar; Antonov, Stoichko; Prosa, Ty J.; Larson, David J.; Francois‐Saint‐Cyr, Hugues; Richardson, Kathleen A.
Abstract: The design of multiphase optical nanocomposites necessitates the understanding of coexisting phases' morphology and chemistry which have deterministic impacts on light–matter interaction. A prominent example is gradient refractive index (GRIN) materials proposed to realize an arbitrarily shaped, single optical component with minimal chromatic aberration. Ge‐As‐Pb‐Se materials are promising for GRIN due to their ability to exhibit spatially varying volume fraction of high‐index Pb‐rich phases in low index matrices. These materials are characterized to date, exclusively using transmission electron microscopy to reveal their phase separation and induced crystalline phase(s). It is found in the study that the intrinsic 2D perspective of the technique has hindered the identification of true morphology. To clarify this ambiguity, atom probe tomography (APT) is utilized to gain the first‐ever observation of the nanocomposites' microstructure and its evolution upon heat treatment in a 3D space. The APT‐quantified geometry and chemistry of coexisting phases are considered to predict the effective media's optical behaviors which closely match experimental data, enabling the establishment of the material's predictive and accurate process–structure–property relationship. Findings in the study demonstrate the robustness and advantage of the APT‐assisted characterization in the design and realization of GRIN materials. Abstract : Ge‐As‐Pb‐Se chalcogenide nanocomposites are used as a testbed material to validate that atom probe tomography provides critical microstructural information in a 3D space. Such knowledge enables the prediction of optical properties which closely match experimental data. This finding establishes the material's process–structure–property relationship, which facilitates optical designs envisioned to realize a lightweight, low‐loss, gradient‐refractive‐index material with minimal spectral aberration.